Agricultural Policy Design and Implementation A Synthesis - van Tongeren, Frank (OECD Publishing, 2008)
Are current agricultural policies based on measurable objectives? Is the current policy set adequately addressing stated objectives? What could an improved agricultural policy set look like, and how to get onto a reform trajectory? These are some of the questions addressed in this publication. It draws on several projects that were undertaken in recent years under the auspices of the OECD Committee for Agriculture and summarizes practical recommendations concerning the pathway to agricultural policy reform. It presents operational characteristics of the policy set that would best achieve domestic policy objectives while minimising distortions and spillovers in international trade
Keywords: Agriculture and Food